Diseño de un Modelo Administrativo- Contable en el Comercial Ellosniner de la Ciudad de Zamora, Periodo del 01 de Enero al 30 de Junio del 2015 - Paredes Maldonado, Leydi Faviola (2016)
This thesis entitled "DESIGN OF AN ADMINISTRATIVE AND ACCOUNTING MODEL IN THE COMMERCIAL ELLOSNINER CITY OF ZAMORA, PERIOD 01 JANUARY TO 30 JUNE 2015" was made to comply with a requirement to obtain the title of Engineer accounting and Auditing, Certified Public Accountant Auditor, developed according to the Regulation of Academic Board of the National University of Loja and a proposal to solve the shortcomings in the accounting area of this micro company dedicated to the sale of goods. It was developed to meet the overall objective is to design an accounting administrative model in the Commercial Ellosniner city of Zamora, period January 1 to June 30, 2015 through the specific objectives. The development of the accounting process to the presentation of financial statements in accordance with the principles of generally accepted accounting Plan and Accounting Manual with their respective coding, description and operation of the accounts was designed after gathering took place the source documents such as invoices for the purchase and sale of commercial Ellosniner with an assistant to then be chronologically recorded transactions in the general subsequently daily ledger to know the balance of each account at the end of the accounting process it was carried out after the completion of the trial balance to verify that the sums of the debit and credit balances totaling equal values to finally present the financial statements to understand the economic and financial situation of the business to make decisions that contribute to efficient development. With the design of a structural organization and functions manual is intended to inform the hierarchical levels, relations between employees and the structure of commercial Ellosniner also regarded by employees as a 5 guide to understanding the rights and obligations to be met in order to better coordination within the business so favors the operation of the business. With the implementation of financial indicators as they are liquidity for the ability to enjoy shopping to meet its obligations in the short term, activity to determine the efficiency that has the trade in the use of its assets, borrowing to measure level of funding and profitability to know how effective management has costs and expenses. The methodology used in this thesis are the methods: scientific, inductive, deductive, analytical, and mathematician who helped them gathering the information necessary and relevant to the implementation of this thesis. With the development of the accounting process to commercial Ellosniner it is to establish adequate controls in the development of the activities of the same to determine the financial and economic situation of the business to guide the owner to make the best decisions aimed at strengthening the trade. In order to take proper control own commercial Ellosniner should hire an accountant so you can implement a system of organization accounting that allows you to have a technical and essential to make better use of the resources you have and make decisions tool appropriate that contribute to the efficient development of commercial Ellosniner.